Draft Genomes of Anopheles cracens and Anopheles maculatus: Comparison of Simian Malaria and Human Malaria Vectors in Peninsular Malaysia. - Yee-Ling Lau; Wenn-Chyau Lee; Junhui Chen; Zhen Zhong; Jianbo Jian; Amirah Amir; Fei-Wen Cheong; Jia-Siang Sum; Mun-Yik Fong (PLoS ONE, 2016)
Anopheles cracens has been incriminated as the vector of human knowlesi malaria in peninsular Malaysia. Besides, it is a good laboratory vector of Plasmodium falciparum and P. vivax. The distribution of An. cracens overlaps with that of An. maculatus, the human malaria vector in peninsular Malaysia that seems to be refractory to P. knowlesi infection in natural settings. Whole genome sequencing was performed on An. cracens and An. maculatus collected here. The draft genome of An. cracens was 395 Mb in size whereas the size of An. maculatus draft genome was 499 Mb. Comparison with the published Malaysian An. maculatus genome suggested the An. maculatus specimen used in this study as a different geographical race. Comparative analyses highlighted the similarities and differences between An. cracens and An. maculatus, providing new insights into their biological behavior and characteristics.